PERKEMBANGAN MORAL SISWA SMP TENTANG PERMASALAHAN PERTANIAN PASANG SURUT DI KABUPATEN BANJAR MELALUI PENYELESAIAN MASALAH - Ruhena Ruhena (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2019)
Moral is the ability to understand values in a society concerning good or bad, right or wrong things, and what should or should not be done by an individual in a society. Moral development of adolescence is a time when teenagers are already more mature and knowledgeable about moral values and the concepts of morality than children. Problem solving can engage students in solving problems systematically to deal with the problem associated with the existing life in the community and surrounding environment. Problems of tidal agriculture were chosen to be the case, so that we can get the moral dilemmas and characteristics of the stages of moral development of students through problem solving. This research is aimed at describing (1) moral development stage of the students of SMP Negeri 1 Gambut concerning issues of tidal agriculture in Kabupaten Banjar through valid and reliable problem solving, (2) the characteristics of moral development stages of the students of SMP Negeri 1 Gambut concerning issues of tidal agriculture in Kabupaten Banjar through valid and reliable problem solving. The method used qualitative approach and descriptive type. The instruments of the research were in the form of initial tests of moral development using Defining Issues Test (DIT), written assignments, and interviews. The samples of the research were students of class VIII SMP Negeri 1 Gambut, Kabupaten Banjar. The results of this research showed that moral development stages of the students of SMP Negeri 1 Gambut concerning the issues of tidal agriculture in Kabupaten Banjar through problem solving were in stages 2, 3 and 4. The characteristics of the moral development stages of the students of SMP Negeri 1 Gambut concerning the issues of tidal agriculture in Kabupaten Banjar through problem solving were the characteristics of stage 2 (self-interest), the characteristics of stage 3 (environmental expectations), and the characteristics of stage 4 (understanding social rules).